Close your eyes and count to 10 ebook A novel. - Unger, Lisa (2025)
"[Unger's] great at keeping you interested and not seeing all the twists that are coming with a fabulous cat-mouse game." —Sarah Michelle Gellar, Emmy-award winning actress An extreme game of hide-and-seek turns deadly in this riveting new thriller from New York Times bestselling author Lisa Unger When the real game begins, who will make it to the count of 10? Charismatic daredevil and extreme adventurer Maverick Dillan invites you to the ultimate game of hide-and-seek. But as the players gather on Falcao Island, the event quickly spirals into a chilling test of survival. A storm rages as a deadly threat stalks the contestants, turning the challenge into something far more sinister than the social media stunt it was intended to be. Enter Adele, a single mother with a fierce determination to protect her children at all costs. When she begins the game, she unwittingly enters a twisted web of deception and intrigue. Can she maneuver through the treacherous storm and the relentless competition and get home to her family? In a ruthless battle for survival where the stakes are higher than ever, the blurry line between the virtual and the real proves that the only person we can trust is ourselves.